PSYCHOLOGICAL BASIS OF INNOVATIVE ACTIVITY AND CREATIVITY OF TEACHERS OF HIGHER EDUCATION INSTITUTIONS - Akilovna, Esanova Maloxat; Sobirovich, Isamitdinov Sodir; Aminovna, Turakulova Feruza; Nadjatbekovna, Kadirova Dildora; Xamidovna, Achilova Soxiba (International Journal of Psychosocial Rehabilitation, 2020)
Understanding the need to reform the education system requires that educational institutions be involved in innovative processes in practice, to see themselves in an innovative space where they have the opportunity to create, and most importantly, to adopt concrete innovations. The role of the teacher in the teaching process is more complex and has its own historical and modern aspects. In the past, teachers were required to provide only modern knowledge, but now they are required to provide educational, cultural, spiritual, political and practical knowledge. This article covers issues such as determining the role of innovative technologies in the development of education, pedagogical justification for the development and implementation of innovative methods in education, the development of scientific and methodological recommendations on the subject.